Self-lubricating cutting fluid and preparation method thereof
Through the molecular structure design of asymmetric branched fluorocarboxylic polyether, a multi-layer lubricating film and composite protective film are constructed, which solves the contradiction between lubricating performance and metal adhesion resistance in cutting fluid, and achieves efficient lubrication and stable processing, which meets the requirements of green manufacturing.
Patent Information
- Application Number
- CN202510635855.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-16
- Publication Date
- 2025-08-19
AI Technical Summary
There is a contradiction between the lubrication performance and metal adhesion resistance of existing cutting fluids, making it difficult to achieve multi-performance synergistic optimization in complex processing scenarios. The traditional cutting fluid has complex components, a lengthy synthesis process, and the products are prone to residual harmful substances, which does not conform to the development trend of green manufacturing.
Asymmetric branched fluorocarboxylic polyether is used as the core component to build a "three-dimensional adsorption-low resistance lubrication" mechanism through molecular structure design to form a multi-layer lubricating film. Combined with the low surface energy characteristics of the fluorocarbon segment and the polar adsorption of carboxyl groups, a composite protective film of "physical barrier + chemical anchoring" is constructed to achieve efficient lubrication and anti-metal adsorption.
Significantly improve the processing surface accuracy and tool life, meet the extreme pressure requirements of high-speed cutting and difficult-to-process materials, reduce metal adhesion and wear, and have environmentally friendly advantages, and meet the requirements of green manufacturing.
Smart Images

Figure CN120505137A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal processing cutting fluids, in particular to a self-lubricating cutting fluid and a preparation method thereof. Background Art
[0002] During metal cutting, cutting fluids, as key auxiliary materials, must simultaneously fulfill multiple functions, including lubrication, cooling, and rust prevention. However, conventional cutting fluids commonly suffer from technical bottlenecks such as insufficient lubrication, weak extreme pressure and anti-wear capabilities, and severe metal adhesion, severely hindering machining efficiency and workpiece surface quality. Existing commercially available cutting fluids often utilize linear polyethers or simple fluorinated additives. Their molecular structures lack steric hindrance, making them easily squeezed out of the lubricating film under high pressure. This results in an increased coefficient of friction and larger wear spot diameters. Furthermore, their maximum no-seizure load is low, and their sintering load is insufficient, making them incapable of meeting the heavy-duty cutting demands of difficult-to-cut materials such as titanium alloys and stainless steel. Particularly under extreme pressure conditions, conventional cutting fluids rely on physical adsorption to form a lubricating film that is susceptible to shear fracture, causing metal cold welding, increased tool wear, and scratches on the workpiece surface. In existing technologies, the lubrication and anti-adhesion properties of cutting fluids often exhibit a mutually restrictive relationship: increasing lubricity requires increasing the content of oiliness agent, but excessive oiliness agent can easily lead to metal particle adsorption; enhancing extreme pressure resistance relies on active elements such as sulfur and phosphorus, which can increase the risk of corrosion. This technical contradiction makes it difficult for cutting fluids to achieve multi-performance synergistic optimization in complex machining scenarios. In addition, traditional cutting fluids have complex components, lengthy synthesis processes, and are prone to residual harmful substances in the products, which is not in line with the development trend of green manufacturing. Summary of the Invention
[0003] In view of this, the purpose of the present invention is to provide a self-lubricating cutting fluid and a preparation method thereof, so as to solve the contradiction between the lubricating performance and the anti-metal adhesion performance of the existing cutting fluid.
[0004] Based on the above purpose, the present invention provides a self-lubricating cutting fluid, comprising the following raw materials in parts by weight: deionized water: 60-70 parts, pH regulator: 5-10 parts, rust inhibitor: 1-3 parts, fungicide: 0.5-1 part, extreme pressure and wear resistant agent: 5-10 parts, asymmetrically branched fluorocarboxylic polyether: 10-20 parts;
[0005] The preparation process of the asymmetrically branched fluorocarboxylic polyether is as follows:
[0006] (1) Under nitrogen protection, pentaerythritol, dimethyl carbonate and potassium carbonate are added to anhydrous tetrahydrofuran, the temperature is raised to 60-70°C, and the mixture is stirred for reaction for 2-4 hours. Dilute hydrochloric acid is added to adjust the pH to neutral, and the mixture is extracted three times with ethyl acetate. The organic phases are combined, dried, and subjected to silica gel column chromatography using gradient elution to obtain pentaerythritol methyl tricarbonate;
[0007] (2) adding pentaerythritol methyl tricarbonate and potassium hydroxide obtained in (1) into a high-pressure reactor, heating to 120-140° C. while stirring, vacuum dehydration, adding ethylene oxide, maintaining the pressure at 0.5-0.8 MPa, reacting for 2-4 hours, then adding propylene oxide and continuing the reaction for 1-3 hours, cooling to 40-50° C., opening the vacuum valve, stirring for 30-60 minutes, adding deionized water, adjusting the pH to neutral with a phosphoric acid solution, filtering and drying to obtain an asymmetric branched polyether;
[0008] (3) Add 1-iodoperfluorooctanoic acid and sodium hydroxide to a water / N,N-dimethylformamide mixed solution, then add tetrabutylammonium bromide, heat to 100-120°C, stir and react for 8-10 hours, cool to room temperature, add dilute hydrochloric acid to adjust the pH to neutral, cool to 0-5°C, filter, wash, and dry to obtain 1-hydroxytetrafluorooctanoic acid;
[0009] (4) adding the asymmetrically branched polyether obtained in (2), 1-hydroxytetradecafluorooctanoic acid obtained in step (3), p-toluenesulfonic acid and toluene into a reactor with a water separator, heating to 110-130° C., stirring and reacting for 5-7 hours, cooling to 0-5° C., filtering, washing the organic phase with sodium bicarbonate solution and deionized water until the pH reaches neutral, and drying to obtain an asymmetrically branched fluoropolyether;
[0010] (5) The asymmetrically branched fluoropolyether, maleic anhydride and xylene obtained in (4) are added to a reactor, heated to 80-90° C., stirred for 3-5 hours, cooled to room temperature, added with deionized water, and the pH is adjusted to neutral with aqueous ammonia. The aqueous phase is separated and collected, dried, and added to ethanol, stirred for 30-60 minutes, filtered, and dried on a rotary evaporator to obtain an asymmetrically branched fluorocarboxylic polyether.
[0011] Preferably, the pH regulator refers to triethanolamine; the rust inhibitor refers to one of triethanolamine oleate soap or sodium dodecylsulfonate; the bactericide refers to one of phenylisothiazolinone or methylisothiazolinone; the extreme pressure and wear-resistant agent refers to one of phenol polyoxyethylene ether phosphate or 4,4-methylenebis(dibutyldithiocarboxamide).
[0012] Preferably, the weight ratio of pentaerythritol, dimethyl carbonate, potassium carbonate and anhydrous tetrahydrofuran in (1) is 1:2.5-3.5:0.05-0.15:8-12, and dilute hydrochloric acid refers to a hydrochloric acid aqueous solution with a concentration of 10%. The reaction equation is as follows:
[0013]
[0014] The product was characterized by H NMR.
[0015] Preferably, the weight ratio of ethyl acetate to anhydrous tetrahydrofuran used in each of the three extractions with ethyl acetate in (1) is 1:2, and the gradient elution refers to the volume ratio of petroleum ether to ethyl acetate in each step of the eluent being successively from 1:0, 30:1, 20:1, 10:1 to 5:1, and the distribution of the product on the thin layer silica gel TLC plate is as follows: Figure 7 shown.
[0016] Preferably, in (2), the weight ratio of pentaerythritol tricarbonate, potassium hydroxide, ethylene oxide, propylene oxide and deionized water is 1:0.005-0.015:4-8:2-4:8-12, and the phosphoric acid solution refers to a 10% phosphoric acid aqueous solution. The reaction equation is as follows:
[0017]
[0018] The product was characterized by FTIR infrared spectroscopy.
[0019] Preferably, the weight ratio of 1-iodoperfluorooctanoic acid, sodium hydroxide, tetrabutylammonium bromide and water / N,N-dimethylformamide mixed solution in (3) is 1:0.05-0.1:0.003-0.007:10-20, and the reaction equation is as follows:
[0020]
[0021] The product was characterized by H NMR.
[0022] Preferably, the water / N,N-dimethylformamide mixed solution in (3) refers to a mixture of water and N,N-dimethylformamide in a weight ratio of 3:1, and the dilute hydrochloric acid refers to a hydrochloric acid aqueous solution with a concentration of 10%.
[0023] Preferably, the weight ratio of the asymmetrically branched polyether, 1-hydroxytetradecanoic acid, p-toluenesulfonic acid and toluene in (4) is 1:0.2-0.4:0.005-0.01:10-20, and the sodium bicarbonate solution refers to a 5% sodium bicarbonate aqueous solution. The reaction equation is as follows:
[0024]
[0025] Product passed 19 The products were characterized by F NMR and H NMR.
[0026] Preferably, the weight ratio of the asymmetrically branched fluoropolyether, maleic anhydride, xylene, deionized water and ethanol in (5) is 1:0.2-0.4:10-20:10-20:3-7, and the reaction equation is as follows:
[0027]
[0028] The product was characterized by H NMR.
[0029] Furthermore, the present invention also provides a method for preparing the self-lubricating cutting fluid, which specifically comprises the following steps:
[0030] S1. Add pH regulator and deionized water to the mixing kettle, stir at 200-300 rpm, mix for 5-10 min, add rust inhibitor, heat to 35-45 ° C, stir for 10-20 min, return to room temperature, add antibacterial agent and stir for 5-10 min to obtain a precursor solution;
[0031] S2. Add asymmetrically branched fluorocarboxylic polyether to the precursor solution obtained in S1, stir at 500-700 rpm, mix for 10-20 minutes, then add extreme pressure and wear resistance agent, mix for 5-10 minutes to obtain a self-lubricating cutting fluid.
[0032] Beneficial effects of the present invention:
[0033] 1. The present invention constructs a composite mechanism of "steric adsorption-low-resistance lubrication" through molecular structure design. The core component, asymmetrically branched fluorocarboxylic polyether, uses pentaerythritol as the skeleton to form a branched structure. Its unique "1 main chain + 3 branches" configuration forms a multi-level lubricating film on the metal surface: the branched skeleton forms a three-dimensional adsorption layer by virtue of the steric effect, and the fluorocarbon segment relies on the low surface energy characteristics to form a molecular-level lubricating barrier between the interfaces, effectively isolating the metal contact and reducing friction resistance. This structure avoids the single-chain tiling defects of traditional linear molecules, allowing the lubricating film to remain intact during high-speed friction, significantly reducing adhesive wear and abrasive wear, and fundamentally improving the machining surface accuracy and extending the tool life. This design achieves efficient lubrication without relying on strong charge adsorption through the synergistic effect of physical steric hindrance and chemical low surface energy, ensuring the stability and precision of the machining process.
[0034] 2. The unique asymmetric branched skeleton in the invention combines a rigid core with flexible segments, which resist molecular chain breakage through steric hindrance under high-pressure conditions and maintain the stability of the lubricating film structure. At the same time, the chemical inertness and high heat resistance of the fluorocarbon segments make them less susceptible to oxidation at high temperatures, synergizing with the polar adsorption of carboxyl groups to construct a composite protective film of "physical barrier + chemical anchoring" on the metal surface. This dual reinforcement mechanism enables the lubricating film to withstand higher loads, effectively inhibiting metal welding and film rupture, meeting the extreme pressure requirements during high-speed cutting and processing of difficult-to-process materials (such as high-strength alloys), and significantly improving the reliability and stability of the processing process.
[0035] 3. Through maleic anhydride modification and ammonia adjustment, the carboxyl group of fluorocarboxylic acid polyether is converted into ionized carboxylic acid ammonium salt (-COO-NH4 +), forming a strongly negatively charged surface in the aqueous phase, which prevents metal particles from adhering to the cutting fluid through electrostatic repulsion. Simultaneously, the multi-chain structure of the branched molecules wraps around particles from multiple directions. Combined with the low surface energy of the fluorocarbon chains, this promotes interfacial wetting, creating a triple dispersion system of "electrostatic repulsion + steric hindrance + micellarization." This design effectively addresses the problem of metal debris adhering to and exacerbating wear in traditional cutting fluids, ensuring the uniformity and effectiveness of the cutting fluid over long-term use and reducing filtration and maintenance costs.
[0036] 4. This invention achieves a balance between lubrication and metal adsorption through a molecular design of "fluorocarbon segments-polyether backbone-carboxylic acid groups." The fluorocarbon segments enhance lubrication efficiency, the polyether backbone enhances water solubility and system compatibility, and the ionized carboxyl groups synergize with pH regulators and rust inhibitors to create a stable water-based system. This formula avoids the high pollution levels of mineral oils in traditional cutting fluids while reducing corrosive components through functional group optimization. It offers broad adaptability to cutting tools and workpiece materials, combining environmental advantages with processing safety, and meets the green manufacturing requirements for low-pollution, long-life cutting fluids. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is the H NMR spectrum of pentaerythritol methyl tricarbonate prepared in Example 2;
[0038] Figure 2 FTIR infrared spectrum of the asymmetrically branched polyether prepared in Example 2;
[0039] Figure 3 This is the H NMR spectrum of 1-hydroxytetradecafluorooctanoic acid prepared in Example 2;
[0040] Figure 4 The asymmetric branched fluoropolyether prepared in Example 2 19 F NMR spectrum;
[0041] Figure 5 This is the H NMR spectrum of the asymmetrically branched fluoropolyether prepared in Example 2;
[0042] Figure 6 This is the H NMR spectrum of the asymmetrically branched fluorocarboxylic acid polyether prepared in Example 2;
[0043] Figure 7 The distribution of the product on a thin layer silica gel TLC plate when preparing pentaerythritol methyl tricarbonate in step (1) of Example 1-6. DETAILED DESCRIPTION
[0044] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to specific embodiments.
[0045] The sources of the reagents and raw materials used in the examples of the present invention are as follows:
[0046] Pentaerythritol was purchased from Tianjin Aoluqi Chemical Technology Co., Ltd. with a purity of 98%; dimethyl carbonate was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. with a purity of 99%; ethylene oxide was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. with a purity of 99%; propylene oxide was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. with a purity of 99%; 1-iodoperfluorooctanoic acid was purchased from Dalian Shuanghang Chemical Co., Ltd. with a purity of 98%; tetrabutylammonium bromide was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. with a purity of 99%; p-toluenesulfonic acid was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. with a purity of 99%; maleic anhydride was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. with a purity of 99%; triethanolamine was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Co., Ltd., with a purity of 99%; triethanolamine oleate soap was purchased from Shanghai Maclean Biochemical Technology Co., Ltd., with a purity of 92%; sodium dodecyl sulfonate was purchased from Shanghai Maclean Biochemical Technology Co., Ltd., with a purity of 98%; phenylisothiazolinone was purchased from Wuhan Xinli Biotechnology Co., Ltd., with a content of >20%; methylisothiazolinone was purchased from Shanghai Haohong Biopharmaceutical Technology Co., Ltd., with a purity of 98%; phenol polyoxyethylene ether phosphate was purchased from Shanghai Maclean Biochemical Technology Co., Ltd., with an acid value of 400-420; 4,4-methylenebis(dibutyldithiocarboxamide) was purchased from Hangzhou Shitean Chemical Co., Ltd., with a purity of 99%; polyethylene oxide propylene oxide monobutyl ether was purchased from Hai'an Petrochemical Plant, Jiangsu Province, with a purity of 99%.
[0047] Example 1: A specific method for preparing a self-lubricating cutting fluid comprises the following steps:
[0048] (1) Under nitrogen protection, 1.2 kg of pentaerythritol, 3 kg of dimethyl carbonate, and 60 g of potassium carbonate were added to 9.6 kg of anhydrous tetrahydrofuran, the temperature was raised to 60° C., and the mixture was stirred for 2 h. A 10% aqueous hydrochloric acid solution was added to adjust the pH to neutral. The mixture was extracted three times with 4.8 kg of ethyl acetate each time. The organic phases were combined, dried, and subjected to silica gel column chromatography using gradient elution to obtain pentaerythritol methyl tricarbonate;
[0049] (2) 600 g of pentaerythritol tricarbonate and 3 g of potassium hydroxide obtained in (1) were added to a high-pressure reactor, heated to 120° C. with stirring, vacuum-dehydrated, 2.4 kg of ethylene oxide was added, the pressure was maintained at 0.5 MPa, and the reaction was continued for 2 h. 1.2 kg of propylene oxide was then added and the reaction was continued for 1 h. The temperature was lowered to 40° C., the vacuum valve was opened, and the reaction was stirred for 30 min. 4.8 kg of deionized water was added, and the pH was adjusted to neutral with a 10% aqueous phosphoric acid solution. The mixture was filtered and dried to obtain an asymmetric branched polyether.
[0050] (3) 1 kg of 1-iodoperfluorooctanoic acid and 50 g of sodium hydroxide were added to 10 kg of a water / N,N-dimethylformamide mixed solution (water and N,N-dimethylformamide were mixed in a weight ratio of 3:1), and then 3 g of tetrabutylammonium bromide was added. The mixture was heated to 100° C., stirred and reacted for 8 h, cooled to room temperature, and a 10% aqueous hydrochloric acid solution was added to adjust the pH to neutral. The mixture was cooled to 0° C., filtered, washed, and dried to obtain 1-hydroxytetrafluorooctanoic acid.
[0051] (4) 2 kg of the asymmetrically branched polyether obtained in step (2), 400 g of 1-hydroxytetradecanoic acid obtained in step (3), 10 g of p-toluenesulfonic acid, and 20 kg of toluene were added to a reactor equipped with a water separator, the temperature was raised to 110° C., the reaction was stirred for 5 h, the reaction was cooled to 0° C., the reaction was filtered, and the organic phase was washed with a 5% aqueous sodium bicarbonate solution and deionized water until the pH value was neutral, and the reaction was dried to obtain an asymmetrically branched fluoropolyether;
[0052] (5) 1.5 kg of the asymmetrically branched fluoropolyether obtained in (4), 300 g of maleic anhydride, and 15 kg of xylene were added to a reactor, heated to 80° C., stirred for 3 h, cooled to room temperature, added with 15 kg of deionized water, adjusted the pH to neutral with aqueous ammonia, separated and collected the aqueous phase, dried, added to 4.5 kg of ethanol, stirred for 30 min, filtered, and dried on a rotary evaporator to obtain an asymmetrically branched fluoropolyether;
[0053] (6) Add 500 g of triethanolamine and 6 kg of deionized water to the blending kettle, stir at 200 rpm, mix for 5 min, add 100 g of triethanolamine oleate soap, heat to 35 ° C, stir for 10 min, return to room temperature, add 50 g of phenylisothiazolinone and stir for 5 min to obtain a precursor solution;
[0054] (7) Add 1 kg of asymmetrically branched fluorocarboxylic polyether to the precursor solution obtained in (6), stir at 500 rpm, mix for 10 min, then add 500 g of phenol polyoxyethylene ether phosphate, mix for 5 min, and obtain a self-lubricating cutting fluid.
[0055] Example 2: A specific method for preparing a self-lubricating cutting fluid comprises the following steps:
[0056] (1) Under nitrogen protection, 1 kg of pentaerythritol, 3 kg of dimethyl carbonate, and 100 g of potassium carbonate were added to 10 kg of anhydrous tetrahydrofuran, the temperature was raised to 65° C., and the mixture was stirred for 3 hours. A 10% aqueous hydrochloric acid solution was added to adjust the pH to neutral. The mixture was extracted three times with 5 kg of ethyl acetate each time. The organic phases were combined, dried, and subjected to silica gel column chromatography using gradient elution to obtain pentaerythritol methyl tricarbonate.
[0057] (2) 500 g of pentaerythritol tricarbonate and 5 g of potassium hydroxide obtained in (1) were added to a high-pressure reactor, heated to 130° C. with stirring, vacuum-dehydrated, 3 kg of ethylene oxide was added, the pressure was maintained at 0.6 MPa, and the reaction was continued for 3 h. 1.5 kg of propylene oxide was then added and the reaction was continued for 2 h. The temperature was lowered to 45° C., the vacuum valve was opened, and the reaction was stirred for 45 min. 5 kg of deionized water was added, and the pH was adjusted to neutral with a 10% aqueous phosphoric acid solution. The mixture was filtered and dried to obtain an asymmetric branched polyether.
[0058] (3) 1 kg of 1-iodoperfluorooctanoic acid and 75 g of sodium hydroxide were added to 15 kg of a water / N,N-dimethylformamide mixed solution (water and N,N-dimethylformamide were mixed in a weight ratio of 3:1), and then 5 g of tetrabutylammonium bromide was added. The mixture was heated to 110° C., stirred for 9 hours, cooled to room temperature, and a 10% aqueous hydrochloric acid solution was added to adjust the pH to neutral. The mixture was cooled to 3° C., filtered, washed, and dried to obtain 1-hydroxytetrafluorooctanoic acid.
[0059] (4) 2.5 kg of the asymmetrically branched polyether obtained in step (2), 750 g of 1-hydroxytetradecafluorooctanoic acid obtained in step (3), 18.75 g of p-toluenesulfonic acid, and 40 kg of toluene were added to a reactor equipped with a water separator, the temperature was raised to 120° C., the reaction was stirred for 6 h, the reaction was cooled to 3° C., the reaction mixture was filtered, and the organic phase was washed with a 5% aqueous sodium bicarbonate solution and deionized water until the pH value was neutral, and the reaction mixture was dried to obtain an asymmetrically branched fluoropolyether;
[0060] (5) 2 kg of the asymmetrically branched fluoropolyether obtained in (4), 600 g of maleic anhydride and 30 kg of xylene were added to a reactor, heated to 85 ° C., stirred for 4 h, cooled to room temperature, added with 30 kg of deionized water, adjusted the pH to neutral with aqueous ammonia, separated and collected the aqueous phase, dried, added to 10 kg of ethanol, stirred for 45 min, filtered, and dried on a rotary evaporator to obtain an asymmetrically branched fluoropolyether;
[0061] (6) Add 750 g of triethanolamine and 6.5 kg of deionized water to the blending kettle, stir at 250 rpm, mix for 8 min, add 200 g of triethanolamine oleate soap, heat to 40 ° C, stir for 15 min, return to room temperature, add 75 g of phenylisothiazolinone and stir for 8 min to obtain a precursor solution;
[0062] (7) Add 1.5 kg of asymmetrically branched fluorocarboxylic polyether to the precursor solution obtained in (6), stir at 600 rpm, mix for 15 min, then add 750 g of phenol polyoxyethylene ether phosphate, mix for 8 min, and obtain a self-lubricating cutting fluid.
[0063] Example 3: A specific method for preparing a self-lubricating cutting fluid comprises the following steps:
[0064] (1) Under nitrogen protection, 2 kg of pentaerythritol, 7 kg of dimethyl carbonate, and 300 g of potassium carbonate were added to 24 kg of anhydrous tetrahydrofuran, the temperature was raised to 70° C., and the mixture was stirred for 5 hours. A 10% aqueous hydrochloric acid solution was added to adjust the pH to neutral. The mixture was extracted three times with 12 kg of ethyl acetate each time. The organic phases were combined, dried, and subjected to silica gel column chromatography using gradient elution to obtain pentaerythritol methyl tricarbonate;
[0065] (2) 1 kg of pentaerythritol tricarbonate and 15 g of potassium hydroxide obtained in (1) were added to a high-pressure reactor, heated to 140° C. with stirring, vacuum-dehydrated, 8 kg of ethylene oxide was added, the pressure was maintained at 0.8 MPa, and the reaction was continued for 4 h. 4 kg of propylene oxide was then added and the reaction was continued for 3 h. The temperature was lowered to 50° C., the vacuum valve was opened, and the reaction was stirred for 60 min. 12 kg of deionized water was added, and the pH was adjusted to neutral with a 10% aqueous phosphoric acid solution. The mixture was filtered and dried to obtain an asymmetric branched polyether.
[0066] (3) 1.6 kg of 1-iodoperfluorooctanoic acid and 160 g of sodium hydroxide were added to 32 kg of a water / N,N-dimethylformamide mixed solution (water and N,N-dimethylformamide were mixed in a weight ratio of 3:1), and then 11.2 g of tetrabutylammonium bromide was added. The mixture was heated to 120° C., stirred for 10 hours, cooled to room temperature, and a 10% aqueous hydrochloric acid solution was added to adjust the pH to neutral. The mixture was cooled to 5° C., filtered, washed, and dried to obtain 1-hydroxytetrafluorooctanoic acid.
[0067] (4) 3.5 kg of the asymmetrically branched polyether obtained in step (2), 1.4 kg of 1-hydroxytetradecafluorooctanoic acid obtained in step (3), 35 g of p-toluenesulfonic acid, and 70 kg of toluene were added to a reactor equipped with a water separator, the temperature was raised to 130° C., the reaction was stirred for 7 hours, the reaction was cooled to 5° C., the reaction mixture was filtered, and the organic phase was washed with a 5% aqueous sodium bicarbonate solution and deionized water until the pH value was neutral, and the reaction mixture was dried to obtain an asymmetrically branched fluoropolyether;
[0068] (5) 3 kg of the asymmetrically branched fluoropolyether obtained in (4), 1.2 kg of maleic anhydride, and 60 kg of xylene were added to a reactor, heated to 90° C., stirred for 5 h, cooled to room temperature, added with 60 kg of deionized water, and the pH was adjusted to neutral with aqueous ammonia. The aqueous phase was separated and collected, dried, and added to 21 kg of ethanol, stirred for 60 min, filtered, and dried on a rotary evaporator to obtain an asymmetrically branched fluoropolyether;
[0069] (6) Add 1 kg of triethanolamine and 7 kg of deionized water to the blending kettle, stir at 300 rpm, mix for 10 min, add 300 g of triethanolamine oleate soap, heat to 45 ° C, stir for 20 min, return to room temperature, add 100 g of phenylisothiazolinone and stir for 10 min to obtain a precursor solution;
[0070] (7) Add 2 kg of asymmetrically branched fluorocarboxylic polyether to the precursor solution obtained in (6), stir at 700 rpm, mix for 20 min, then add 1 kg of phenol polyoxyethylene ether phosphate, mix for 10 min, and obtain a self-lubricating cutting fluid.
[0071] Example 4: A specific method for preparing a self-lubricating cutting fluid comprises the following steps:
[0072] (1) Under nitrogen protection, 1 kg of pentaerythritol, 3 kg of dimethyl carbonate, and 100 g of potassium carbonate were added to 10 kg of anhydrous tetrahydrofuran, the temperature was raised to 65° C., and the mixture was stirred for 3 hours. A 10% aqueous hydrochloric acid solution was added to adjust the pH to neutral. The mixture was extracted three times with 5 kg of ethyl acetate each time. The organic phases were combined, dried, and subjected to silica gel column chromatography using gradient elution to obtain pentaerythritol methyl tricarbonate.
[0073] (2) 500 g of pentaerythritol tricarbonate and 5 g of potassium hydroxide obtained in (1) were added to a high-pressure reactor, heated to 130° C. with stirring, vacuum-dehydrated, 3 kg of ethylene oxide was added, the pressure was maintained at 0.6 MPa, and the reaction was continued for 3 h. 1.5 kg of propylene oxide was then added and the reaction was continued for 2 h. The temperature was lowered to 45° C., the vacuum valve was opened, and the reaction was stirred for 45 min. 5 kg of deionized water was added, and the pH was adjusted to neutral with a 10% aqueous phosphoric acid solution. The mixture was filtered and dried to obtain an asymmetric branched polyether.
[0074] (3) 1 kg of 1-iodoperfluorooctanoic acid and 75 g of sodium hydroxide were added to 15 kg of a water / N,N-dimethylformamide mixed solution (water and N,N-dimethylformamide were mixed in a weight ratio of 3:1), and then 5 g of tetrabutylammonium bromide was added. The mixture was heated to 110° C., stirred for 9 hours, cooled to room temperature, and a 10% aqueous hydrochloric acid solution was added to adjust the pH to neutral. The mixture was cooled to 3° C., filtered, washed, and dried to obtain 1-hydroxytetrafluorooctanoic acid.
[0075] (4) 2.5 kg of the asymmetrically branched polyether obtained in step (2), 750 g of 1-hydroxytetradecafluorooctanoic acid obtained in step (3), 18.75 g of p-toluenesulfonic acid, and 40 kg of toluene were added to a reactor equipped with a water separator, the temperature was raised to 120° C., the reaction was stirred for 6 h, the reaction was cooled to 3° C., the reaction mixture was filtered, and the organic phase was washed with a 5% aqueous sodium bicarbonate solution and deionized water until the pH value was neutral, and the reaction mixture was dried to obtain an asymmetrically branched fluoropolyether;
[0076] (5) 2 kg of the asymmetrically branched fluoropolyether obtained in (4), 600 g of maleic anhydride and 30 kg of xylene were added to a reactor, heated to 85 ° C., stirred for 4 h, cooled to room temperature, added with 30 kg of deionized water, adjusted the pH to neutral with aqueous ammonia, separated and collected the aqueous phase, dried, added to 10 kg of ethanol, stirred for 45 min, filtered, and dried on a rotary evaporator to obtain an asymmetrically branched fluoropolyether;
[0077] (6) Add 750 g of triethanolamine and 6.5 kg of deionized water to the blending kettle, stir at 250 rpm, mix for 8 min, add 200 g of sodium dodecylsulfonate, heat to 40 ° C, stir for 15 min, return to room temperature, add 75 g of phenylisothiazolinone and stir for 8 min to obtain a precursor solution;
[0078] (7) Add 1.5 kg of asymmetrically branched fluorocarboxylic polyether to the precursor solution obtained in (6), stir at 600 rpm, mix for 15 min, then add 750 g of phenol polyoxyethylene ether phosphate, mix for 8 min, and obtain a self-lubricating cutting fluid.
[0079] Example 5: A specific method for preparing a self-lubricating cutting fluid comprises the following steps:
[0080] (1) Under nitrogen protection, 1 kg of pentaerythritol, 3 kg of dimethyl carbonate, and 100 g of potassium carbonate were added to 10 kg of anhydrous tetrahydrofuran, the temperature was raised to 65° C., and the mixture was stirred for 3 hours. A 10% aqueous hydrochloric acid solution was added to adjust the pH to neutral. The mixture was extracted three times with 5 kg of ethyl acetate each time. The organic phases were combined, dried, and subjected to silica gel column chromatography using gradient elution to obtain pentaerythritol methyl tricarbonate.
[0081] (2) 500 g of pentaerythritol tricarbonate and 5 g of potassium hydroxide obtained in (1) were added to a high-pressure reactor, heated to 130° C. with stirring, vacuum-dehydrated, 3 kg of ethylene oxide was added, the pressure was maintained at 0.6 MPa, and the reaction was continued for 3 h. 1.5 kg of propylene oxide was then added and the reaction was continued for 2 h. The temperature was lowered to 45° C., the vacuum valve was opened, and the reaction was stirred for 45 min. 5 kg of deionized water was added, and the pH was adjusted to neutral with a 10% aqueous phosphoric acid solution. The mixture was filtered and dried to obtain an asymmetric branched polyether.
[0082] (3) 1 kg of 1-iodoperfluorooctanoic acid and 75 g of sodium hydroxide were added to 15 kg of a water / N,N-dimethylformamide mixed solution (water and N,N-dimethylformamide were mixed in a weight ratio of 3:1), and then 5 g of tetrabutylammonium bromide was added. The mixture was heated to 110° C., stirred for 9 hours, cooled to room temperature, and a 10% aqueous hydrochloric acid solution was added to adjust the pH to neutral. The mixture was cooled to 3° C., filtered, washed, and dried to obtain 1-hydroxytetrafluorooctanoic acid.
[0083] (4) 2.5 kg of the asymmetrically branched polyether obtained in step (2), 750 g of 1-hydroxytetradecafluorooctanoic acid obtained in step (3), 18.75 g of p-toluenesulfonic acid, and 40 kg of toluene were added to a reactor equipped with a water separator, the temperature was raised to 120° C., the reaction was stirred for 6 h, the reaction was cooled to 3° C., the reaction mixture was filtered, and the organic phase was washed with a 5% aqueous sodium bicarbonate solution and deionized water until the pH value was neutral, and the reaction mixture was dried to obtain an asymmetrically branched fluoropolyether;
[0084] (5) 2 kg of the asymmetrically branched fluoropolyether obtained in (4), 600 g of maleic anhydride and 30 kg of xylene were added to a reactor, heated to 85 ° C., stirred for 4 h, cooled to room temperature, added with 30 kg of deionized water, adjusted the pH to neutral with aqueous ammonia, separated and collected the aqueous phase, dried, added to 10 kg of ethanol, stirred for 45 min, filtered, and dried on a rotary evaporator to obtain an asymmetrically branched fluoropolyether;
[0085] (6) Add 750 g of triethanolamine and 6.5 kg of deionized water to the blending kettle, stir at 250 rpm, mix for 8 min, add 200 g of triethanolamine oleate soap, heat to 40 ° C, stir for 15 min, return to room temperature, add 75 g of methylisothiazolinone and stir for 8 min to obtain a precursor solution;
[0086] (7) Add 1.5 kg of asymmetrically branched fluorocarboxylic polyether to the precursor solution obtained in (6), stir at 600 rpm, mix for 15 min, then add 750 g of phenol polyoxyethylene ether phosphate, mix for 8 min, and obtain a self-lubricating cutting fluid.
[0087] Example 6: A specific method for preparing a self-lubricating cutting fluid comprises the following steps:
[0088] (1) Under nitrogen protection, 1 kg of pentaerythritol, 3 kg of dimethyl carbonate, and 100 g of potassium carbonate were added to 10 kg of anhydrous tetrahydrofuran, the temperature was raised to 65° C., and the mixture was stirred for 3 hours. A 10% aqueous hydrochloric acid solution was added to adjust the pH to neutral. The mixture was extracted three times with 5 kg of ethyl acetate each time. The organic phases were combined, dried, and subjected to silica gel column chromatography using gradient elution to obtain pentaerythritol methyl tricarbonate.
[0089] (2) 500 g of pentaerythritol tricarbonate and 5 g of potassium hydroxide obtained in (1) were added to a high-pressure reactor, heated to 130° C. with stirring, vacuum-dehydrated, 3 kg of ethylene oxide was added, the pressure was maintained at 0.6 MPa, and the reaction was continued for 3 h. 1.5 kg of propylene oxide was then added and the reaction was continued for 2 h. The temperature was lowered to 45° C., the vacuum valve was opened, and the reaction was stirred for 45 min. 5 kg of deionized water was added, and the pH was adjusted to neutral with a 10% aqueous phosphoric acid solution. The mixture was filtered and dried to obtain an asymmetric branched polyether.
[0090] (3) 1 kg of 1-iodoperfluorooctanoic acid and 75 g of sodium hydroxide were added to 15 kg of a water / N,N-dimethylformamide mixed solution (water and N,N-dimethylformamide were mixed in a weight ratio of 3:1), and then 5 g of tetrabutylammonium bromide was added. The mixture was heated to 110° C., stirred for 9 hours, cooled to room temperature, and a 10% aqueous hydrochloric acid solution was added to adjust the pH to neutral. The mixture was cooled to 3° C., filtered, washed, and dried to obtain 1-hydroxytetrafluorooctanoic acid.
[0091] (4) 2.5 kg of the asymmetrically branched polyether obtained in step (2), 750 g of 1-hydroxytetradecafluorooctanoic acid obtained in step (3), 18.75 g of p-toluenesulfonic acid, and 40 kg of toluene were added to a reactor equipped with a water separator, the temperature was raised to 120° C., the reaction was stirred for 6 h, the reaction was cooled to 3° C., the reaction mixture was filtered, and the organic phase was washed with a 5% aqueous sodium bicarbonate solution and deionized water until the pH value was neutral, and the reaction mixture was dried to obtain an asymmetrically branched fluoropolyether;
[0092] (5) 2 kg of the asymmetrically branched fluoropolyether obtained in (4), 600 g of maleic anhydride and 30 kg of xylene were added to a reactor, heated to 85 ° C., stirred for 4 h, cooled to room temperature, added with 30 kg of deionized water, adjusted the pH to neutral with aqueous ammonia, separated and collected the aqueous phase, dried, added to 10 kg of ethanol, stirred for 45 min, filtered, and dried on a rotary evaporator to obtain an asymmetrically branched fluoropolyether;
[0093] (6) Add 750 g of triethanolamine and 6.5 kg of deionized water to the blending kettle, stir at 250 rpm, mix for 8 min, add 200 g of triethanolamine oleate soap, heat to 40 ° C, stir for 15 min, return to room temperature, add 75 g of phenylisothiazolinone and stir for 8 min to obtain a precursor solution;
[0094] (7) 1.5 kg of asymmetrically branched fluorocarboxylic polyether was added to the precursor solution obtained in (6), stirred at 600 rpm, mixed for 15 min, and then 750 g of 4,4-methylenebis(dibutyldithioformamide) was added and mixed for 8 min to obtain a self-lubricating cutting fluid.
[0095] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that dimethyl carbonate is not added to protect the hydroxyl group of pentaerythritol. The specific preparation process is as follows: A specific preparation method of a self-lubricating cutting fluid comprises the following steps:
[0096] (1) 500 g of pentaerythritol and 5 g of potassium hydroxide were added to an autoclave, heated to 130° C. under stirring, vacuumed and dehydrated, 3 kg of ethylene oxide was added, the pressure was maintained at 0.6 MPa, and the reaction was continued for 3 h. 1.5 kg of propylene oxide was then added and the reaction was continued for 2 h. The temperature was lowered to 45° C., the vacuum valve was opened, and the reaction was continued for 45 min. 5 kg of deionized water was added, and the pH was adjusted to neutral with a 10% aqueous phosphoric acid solution. The branched polyether was filtered and dried to obtain the branched polyether. Due to the high degree of branching and the complex structure of the product, the viscosity of the obtained branched polyether was significantly improved, and there was a tendency for gelation conversion;
[0097] (2) 1 kg of 1-iodoperfluorooctanoic acid and 75 g of sodium hydroxide were added to 15 kg of a water / N,N-dimethylformamide mixed solution (water and N,N-dimethylformamide were mixed in a weight ratio of 3:1), and then 5 g of tetrabutylammonium bromide was added. The mixture was heated to 110° C., stirred for 9 hours, cooled to room temperature, and a 10% aqueous hydrochloric acid solution was added to adjust the pH to neutral. The mixture was cooled to 3° C., filtered, washed, and dried to obtain 1-hydroxytetrafluorooctanoic acid.
[0098] (3) 2.5 kg of the branched polyether obtained in step (2), 750 g of 1-hydroxytetradecafluorooctanoic acid obtained in step (2), 18.75 g of p-toluenesulfonic acid and 40 kg of toluene were added to a reactor with a water separator, the temperature was raised to 120° C., the reaction was stirred for 6 h, the reaction was cooled to 3° C., the reaction was filtered, and the organic phase was washed with a 5% aqueous sodium bicarbonate solution and deionized water until the pH was neutral, and the reaction was dried to obtain an asymmetric branched fluoropolyether;
[0099] (4) 2 kg of the branched fluoropolyether obtained in (3), 600 g of maleic anhydride and 30 kg of xylene were added to a reactor, heated to 85 ° C., stirred for 4 h, cooled to room temperature, added with 30 kg of deionized water, adjusted the pH to neutral with aqueous ammonia, separated and collected the aqueous phase, dried and added to 10 kg of ethanol, stirred for 45 min, filtered, and dried on a rotary evaporator to obtain an asymmetric branched fluoropolyether;
[0100] (5) Add 750 g of triethanolamine and 6.5 kg of deionized water to the blending kettle, stir at 250 rpm, mix for 8 min, add 200 g of triethanolamine oleate soap, heat to 40 ° C, stir for 15 min, return to room temperature, add 75 g of phenylisothiazolinone and stir for 8 min to obtain a precursor solution;
[0101] (6) Add 1.5 kg of branched fluorocarboxylic polyether to the precursor solution obtained in (5), stir at 600 rpm, mix for 15 minutes, then add 750 g of phenol polyoxyethylene ether phosphate, mix for 8 minutes to obtain a self-lubricating cutting fluid.
[0102] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that linear polyether is used. The specific preparation method is as follows: A specific preparation method of a self-lubricating cutting fluid comprises the following steps:
[0103] (1) 1 kg of 1-iodoperfluorooctanoic acid and 75 g of sodium hydroxide were added to 15 kg of a water / N,N-dimethylformamide mixed solution (water and N,N-dimethylformamide were mixed in a weight ratio of 3:1), and then 5 g of tetrabutylammonium bromide was added. The mixture was heated to 110° C., stirred for 9 hours, cooled to room temperature, and a 10% aqueous hydrochloric acid solution was added to adjust the pH to neutral. The mixture was cooled to 3° C., filtered, washed, and dried to obtain 1-hydroxytetrafluorooctanoic acid.
[0104] (2) 2.5 kg of polyethylene oxide propylene oxide monobutyl ether, 750 g of 1-hydroxytetradecafluorooctanoic acid obtained in step (1), 18.75 g of p-toluenesulfonic acid and 40 kg of toluene were added to a reactor with a water separator, the temperature was raised to 120° C., stirred for reaction for 6 h, cooled to 3° C., filtered, and the organic phase was washed with a 5% sodium bicarbonate aqueous solution and deionized water until the pH reached neutral, and dried to obtain a linear fluoropolyether;
[0105] (3) 2 kg of the linear fluoropolyether obtained in (2), 600 g of maleic anhydride and 30 kg of xylene were added to a reactor, heated to 85° C., stirred for 4 h, cooled to room temperature, added with 30 kg of deionized water, adjusted the pH to neutral with aqueous ammonia, separated and collected the aqueous phase, dried, added to 10 kg of ethanol, stirred for 45 min, filtered, and dried on a rotary evaporator to obtain the linear fluoropolyether;
[0106] (4) Add 750 g of triethanolamine and 6.5 kg of deionized water to the blending kettle, stir at 250 rpm, mix for 8 min, add 200 g of triethanolamine oleate soap, heat to 40 ° C, stir for 15 min, return to room temperature, add 75 g of phenylisothiazolinone and stir for 8 min to obtain a precursor solution;
[0107] (5) Add 1.5 kg of linear fluorocarboxylic polyether to the precursor solution obtained in (4), stir at 600 rpm, mix for 15 minutes, then add 750 g of phenol polyoxyethylene ether phosphate, mix for 8 minutes to obtain a self-lubricating cutting fluid.
[0108] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that the asymmetrically branched polyether is not modified with 1-hydroxytetradecafluorooctanoic acid. The specific preparation method is as follows: A specific preparation method of a self-lubricating cutting fluid comprises the following steps:
[0109] (1) Under nitrogen protection, 1 kg of pentaerythritol, 3 kg of dimethyl carbonate, and 100 g of potassium carbonate were added to 10 kg of anhydrous tetrahydrofuran, the temperature was raised to 65° C., and the mixture was stirred for 3 hours. A 10% aqueous hydrochloric acid solution was added to adjust the pH to neutral. The mixture was extracted three times with 5 kg of ethyl acetate each time. The organic phases were combined, dried, and subjected to silica gel column chromatography using gradient elution to obtain pentaerythritol methyl tricarbonate.
[0110] (2) 500 g of pentaerythritol tricarbonate and 5 g of potassium hydroxide obtained in (1) were added to a high-pressure reactor, heated to 130° C. with stirring, vacuum-dehydrated, 3 kg of ethylene oxide was added, the pressure was maintained at 0.6 MPa, and the reaction was continued for 3 h. 1.5 kg of propylene oxide was then added and the reaction was continued for 2 h. The temperature was lowered to 45° C., the vacuum valve was opened, and the reaction was stirred for 45 min. 5 kg of deionized water was added, and the pH was adjusted to neutral with a 10% aqueous phosphoric acid solution. The mixture was filtered and dried to obtain an asymmetric branched polyether.
[0111] (3) 2 kg of the asymmetrically branched polyether obtained in (2), 600 g of maleic anhydride and 30 kg of xylene were added to a reactor, the temperature was raised to 85° C., the mixture was stirred for 4 h, and the mixture was cooled to room temperature. 30 kg of deionized water was added, the pH was adjusted to neutral with aqueous ammonia, the aqueous phase was separated and collected, dried, added to 10 kg of ethanol, stirred for 45 min, filtered, and dried on a rotary evaporator to obtain an asymmetrically branched carboxylic polyether;
[0112] (4) Add 750 g of triethanolamine and 6.5 kg of deionized water to the blending kettle, stir at 250 rpm, mix for 8 min, add 200 g of triethanolamine oleate soap, heat to 40 ° C, stir for 15 min, return to room temperature, add 75 g of phenylisothiazolinone and stir for 8 min to obtain a precursor solution;
[0113] (5) Add 1.5 kg of asymmetrically branched carboxylic acid polyether to the precursor solution obtained in (4), stir at 600 rpm, mix for 15 minutes, then add 750 g of phenol polyoxyethylene ether phosphate, mix for 8 minutes to obtain a self-lubricating cutting fluid.
[0114] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that the asymmetrically branched fluoropolyether is not modified with maleic anhydride. The specific preparation method is as follows: A specific preparation method of a self-lubricating cutting fluid comprises the following steps:
[0115] (1) Under nitrogen protection, 1 kg of pentaerythritol, 3 kg of dimethyl carbonate, and 100 g of potassium carbonate were added to 10 kg of anhydrous tetrahydrofuran, the temperature was raised to 65° C., and the mixture was stirred for 3 hours. A 10% aqueous hydrochloric acid solution was added to adjust the pH to neutral. The mixture was extracted three times with 5 kg of ethyl acetate each time. The organic phases were combined, dried, and subjected to silica gel column chromatography using gradient elution to obtain pentaerythritol methyl tricarbonate.
[0116] (2) 500 g of pentaerythritol tricarbonate and 5 g of potassium hydroxide obtained in (1) were added to a high-pressure reactor, heated to 130° C. with stirring, vacuum-dehydrated, 3 kg of ethylene oxide was added, the pressure was maintained at 0.6 MPa, and the reaction was continued for 3 h. 1.5 kg of propylene oxide was then added and the reaction was continued for 2 h. The temperature was lowered to 45° C., the vacuum valve was opened, and the reaction was stirred for 45 min. 5 kg of deionized water was added, and the pH was adjusted to neutral with a 10% aqueous phosphoric acid solution. The mixture was filtered and dried to obtain an asymmetric branched polyether.
[0117] (3) 1 kg of 1-iodoperfluorooctanoic acid and 75 g of sodium hydroxide were added to 15 kg of a water / N,N-dimethylformamide mixed solution (water and N,N-dimethylformamide were mixed in a weight ratio of 3:1), and then 5 g of tetrabutylammonium bromide was added. The mixture was heated to 110° C., stirred for 9 hours, cooled to room temperature, and a 10% aqueous hydrochloric acid solution was added to adjust the pH to neutral. The mixture was cooled to 3° C., filtered, washed, and dried to obtain 1-hydroxytetrafluorooctanoic acid.
[0118] (4) 2.5 kg of the asymmetrically branched polyether obtained in step (2), 750 g of 1-hydroxytetradecafluorooctanoic acid obtained in step (3), 18.75 g of p-toluenesulfonic acid, and 40 kg of toluene were added to a reactor equipped with a water separator, the temperature was raised to 120° C., the reaction was stirred for 6 h, the reaction was cooled to 3° C., the reaction mixture was filtered, and the organic phase was washed with a 5% aqueous sodium bicarbonate solution and deionized water until the pH value was neutral, and the reaction mixture was dried to obtain an asymmetrically branched fluoropolyether;
[0119] (5) Add 750 g of triethanolamine and 6.5 kg of deionized water to the blending kettle, stir at 250 rpm, mix for 8 min, add 200 g of triethanolamine oleate soap, heat to 40 ° C, stir for 15 min, return to room temperature, add 75 g of phenylisothiazolinone and stir for 8 min to obtain a precursor solution;
[0120] (6) Add 1.5 kg of asymmetrically branched fluoropolyether to the precursor solution obtained in (5), stir at 600 rpm, mix for 15 min, then add 750 g of phenol polyoxyethylene ether phosphate, mix for 8 min, and obtain a self-lubricating cutting fluid.
[0121] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that after the asymmetrically branched fluorocarboxylic acid polyether is modified with maleic anhydride, no ammonia water is added to adjust the pH to neutral. The specific preparation method is as follows: A specific preparation method of a self-lubricating cutting fluid comprises the following steps:
[0122] (1) Under nitrogen protection, 1 kg of pentaerythritol, 3 kg of dimethyl carbonate, and 100 g of potassium carbonate were added to 10 kg of anhydrous tetrahydrofuran, the temperature was raised to 65° C., and the mixture was stirred for 3 hours. A 10% aqueous hydrochloric acid solution was added to adjust the pH to neutral. The mixture was extracted three times with 5 kg of ethyl acetate each time. The organic phases were combined, dried, and subjected to silica gel column chromatography using gradient elution to obtain pentaerythritol methyl tricarbonate.
[0123] (2) 500 g of pentaerythritol tricarbonate and 5 g of potassium hydroxide obtained in (1) were added to a high-pressure reactor, heated to 130° C. with stirring, vacuum-dehydrated, 3 kg of ethylene oxide was added, the pressure was maintained at 0.6 MPa, and the reaction was continued for 3 h. 1.5 kg of propylene oxide was then added and the reaction was continued for 2 h. The temperature was lowered to 45° C., the vacuum valve was opened, and the reaction was stirred for 45 min. 5 kg of deionized water was added, and the pH was adjusted to neutral with a 10% aqueous phosphoric acid solution. The mixture was filtered and dried to obtain an asymmetric branched polyether.
[0124] (3) 1 kg of 1-iodoperfluorooctanoic acid and 75 g of sodium hydroxide were added to 15 kg of a water / N,N-dimethylformamide mixed solution (water and N,N-dimethylformamide were mixed in a weight ratio of 3:1), and then 5 g of tetrabutylammonium bromide was added. The mixture was heated to 110° C., stirred for 9 hours, cooled to room temperature, and a 10% aqueous hydrochloric acid solution was added to adjust the pH to neutral. The mixture was cooled to 3° C., filtered, washed, and dried to obtain 1-hydroxytetrafluorooctanoic acid.
[0125] (4) 2.5 kg of the asymmetrically branched polyether obtained in step (2), 750 g of 1-hydroxytetradecafluorooctanoic acid obtained in step (3), 18.75 g of p-toluenesulfonic acid, and 40 kg of toluene were added to a reactor equipped with a water separator, the temperature was raised to 120° C., the reaction was stirred for 6 h, the reaction was cooled to 3° C., the reaction mixture was filtered, and the organic phase was washed with a 5% aqueous sodium bicarbonate solution and deionized water until the pH value was neutral, and the reaction mixture was dried to obtain an asymmetrically branched fluoropolyether;
[0126] (5) 2 kg of the asymmetrically branched fluoropolyether obtained in (4), 600 g of maleic anhydride, and 30 kg of xylene were added to a reactor, heated to 85° C., stirred for 4 h, cooled to room temperature, and toluene was removed by vacuum distillation. 10 kg of dichloromethane was added, and the mixture was washed with deionized water. The organic phase was dried on a rotary evaporator to obtain an asymmetrically branched fluoropolyether.
[0127] (6) Add 750 g of triethanolamine and 6.5 kg of deionized water to the blending kettle, stir at 250 rpm, mix for 8 min, add 200 g of triethanolamine oleate soap, heat to 40 ° C, stir for 15 min, return to room temperature, add 75 g of phenylisothiazolinone and stir for 8 min to obtain a precursor solution;
[0128] (7) Add 1.5 kg of asymmetrically branched fluorocarboxylic polyether to the precursor solution obtained in (6), stir at 600 rpm, mix for 15 min, then add 750 g of phenol polyoxyethylene ether phosphate, mix for 8 min, and obtain a self-lubricating cutting fluid.
[0129] Comparative Example 6: The difference between Comparative Example 6 and Example 2 is that a self-lubricating cutting fluid is directly prepared using linear polyether. The specific preparation method is as follows: A specific preparation method of a self-lubricating cutting fluid comprises the following steps:
[0130] (1) Add 750 g of triethanolamine and 6.5 kg of deionized water to a blending kettle, stir at 250 rpm, mix for 8 min, add 200 g of triethanolamine oleate soap, heat to 40 ° C, stir for 15 min, return to room temperature, add 75 g of phenylisothiazolinone and stir for 8 min to obtain a precursor solution;
[0131] (2) Add 1.5 kg of polyethylene oxide propylene oxide monobutyl ether to the precursor solution obtained in (1), stir at 600 rpm, mix for 15 minutes, then add 750 g of phenol polyoxyethylene ether phosphate, mix for 8 minutes to obtain a self-lubricating cutting fluid.
[0132] Performance testing:
[0133] 1. Lubrication performance test: Using a four-ball friction tester, set the parameters load 100N, speed 1200rpm, time 30min, and conduct friction performance tests on the cutting fluids prepared in Examples 1-6 and Comparative Examples 1-6, and record the friction coefficient between the steel balls. and wear spot diameter d. The experimental results are shown in Table 1.
[0134] 2. Extrusion friction performance test: Using a four-ball friction tester, according to the test standard of GB / T 3142-2019, the cutting fluids prepared in Examples 1-6 and Comparative Examples 1-6 were tested for maximum no-seizure load P B Test and sintering load P D Test,The experimental results are shown in Table 1.
[0135] 3. Metal Adhesion Test: 500 ml of the cutting fluid prepared in Examples 1-6 and Comparative Examples 1-6 was added to a beaker, 10 g of metal powder was added, the temperature was raised to 60°C, and the mixture was vigorously stirred at 1000 rpm for 60 min to ensure that the metal powder was fully dispersed in the cutting fluid. The mixture was allowed to stand for 24 h, and the supernatant and precipitate were separated. The supernatant was diluted with water, and the insoluble matter was collected by filtration. The insoluble matter was dried and weighed, recorded as m, and the metal adhesion rate was calculated. The experimental results are shown in Table 1.
[0136] Table 1 Performance test
[0137]
[0138] Performance Analysis:
[0139] It can be seen from the experimental data in Table 1 that the self-lubricating cutting fluids prepared by the present invention in Examples 1-6 have good lubrication performance and extreme pressure friction performance as well as extremely low metal adhesion rate, among which Example 2 has the best comprehensive performance.
[0140] From the perspective of lubrication performance, the self-lubricating cutting fluid prepared in Example 2 has low friction resistance and low wear. This may be because the asymmetric branched fluorocarboxylic acid polyether in Example 2 is based on pentaerythritol as the core to form a branched structure of "1 main chain + 3 side chains", which avoids excessive branching to form highly cross-linked products with complex structures, resulting in poor water solubility or dispersibility and thus reduced lubrication performance; avoids side reactions and improves reaction efficiency, reduces cross-linking and by-products, and facilitates separation and purification; the fluorocarbon chains spread laterally to form a low surface energy lubricating layer, reducing direct contact between metals, while comparative examples 1-6 cannot form an ordered lubricating film due to disordered or linear structures and incomplete modification, and are prone to adhesive wear during friction, resulting in a significant increase in the friction coefficient μ and the wear spot diameter d.
[0141] From the perspective of extreme pressure friction performance, the experimental data in Table 1 show that the self-lubricating cutting fluid prepared in Example 2 has strong shear resistance under high pressure. This may be due to the extreme pressure resistance structural advantage of the branched skeleton: the "core-shell" rigidity (pentaerythritol core) and flexibility (polyether segment) of the asymmetric branched structure are balanced, resisting molecular chain breakage through steric hindrance under high pressure and maintaining film integrity. The interfacial strengthening effect of the fluorocarbon chain and the carboxyl group: The low surface energy and high chemical stability of the fluorocarbon chain form a "physical barrier" under high temperature and high pressure, reducing metal welding. Ammonia adjustment promotes the complete ionization of the carboxyl group and its reaction with the extreme pressure wear-resistant agent (such as phenol polyoxyethylene ether phosphate) to form a composite film containing phosphorus-oxygen-carboxylic acid coordination bonds, which has both lubrication and anti-welding capabilities.
[0142] From the metal adhesion rate, it can be seen that the metal particles in the self-lubricating cutting fluid prepared in Example 2 are highly dispersed in the cutting fluid, and almost no agglomeration and surface adhesion occur. This may be because the ammonia water neutralizes the carboxyl group (-COOH) to form ammonium carboxylate (-CO - NH4 + ), so that the hydrophilic end of fluorocarboxylic polyether carries a negative charge, which is adsorbed on the surface of metal particles. The electrostatic repulsion between particles is significantly higher than the van der Waals attraction, which fundamentally prevents agglomeration and sedimentation. At the same time, the carboxylate radical of the rust inhibitor (such as triethanolamine oleic acid soap) is synchronously ionized, and its hydrophilic end (-COO - ) and fluorocarboxylic acid polyether (-COO -) work synergistically, combined with the steric hindrance of the branched structure, to construct a repulsive dispersion system, making it difficult for metal particles to be wrapped in the cutting fluid. They can be removed by precipitation after standing. In the comparative example, due to the lack of charge repulsion, the particles quickly agglomerated and were coated in the cutting fluid, resulting in an increase in the metal adhesion rate.
[0143] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Within the scope of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A self-lubricating cutting fluid, characterized in that: The invention comprises the following raw materials in parts by weight: deionized water: 60-70 parts, pH regulator: 5-10 parts, rust inhibitor: 1-3 parts, fungicide: 0.5-1 part, extreme pressure and wear-resistant agent: 5-10 parts, asymmetrically branched fluorocarboxylic polyether: 10-20 parts; The preparation process of the asymmetrically branched fluorocarboxylic polyether is as follows: (1) Under nitrogen protection, pentaerythritol, dimethyl carbonate and potassium carbonate are added to anhydrous tetrahydrofuran, the temperature is raised to 60-70°C, and the mixture is stirred for reaction for 2-4 hours. Dilute hydrochloric acid is added to adjust the pH to neutral, and the mixture is extracted three times with ethyl acetate. The organic phases are combined, dried, and subjected to silica gel column chromatography using gradient elution to obtain pentaerythritol methyl tricarbonate; (2) adding pentaerythritol methyl tricarbonate and potassium hydroxide obtained in (1) into a high-pressure reactor, heating to 120-140° C. while stirring, vacuum dehydration, adding ethylene oxide, maintaining the pressure at 0.5-0.8 MPa, reacting for 2-4 hours, then adding propylene oxide and continuing the reaction for 1-3 hours, cooling to 40-50° C., opening the vacuum valve, stirring for 30-60 minutes, adding deionized water, adjusting the pH to neutral with a phosphoric acid solution, filtering and drying to obtain an asymmetric branched polyether; (3) Add 1-iodoperfluorooctanoic acid and sodium hydroxide to a water / N,N-dimethylformamide mixed solution, then add tetrabutylammonium bromide, heat to 100-120°C, stir and react for 8-10 hours, cool to room temperature, add dilute hydrochloric acid to adjust the pH to neutral, cool to 0-5°C, filter, wash, and dry to obtain 1-hydroxytetrafluorooctanoic acid; (4) adding the asymmetrically branched polyether obtained in (2), 1-hydroxytetradecafluorooctanoic acid obtained in step (3), p-toluenesulfonic acid and toluene into a reactor with a water separator, heating to 110-130° C., stirring and reacting for 5-7 hours, cooling to 0-5° C., filtering, washing the organic phase with sodium bicarbonate solution and deionized water until the pH reaches neutral, and drying to obtain an asymmetrically branched fluoropolyether; (5) The asymmetrically branched fluoropolyether, maleic anhydride and xylene obtained in (4) are added to a reactor, heated to 80-90° C., stirred for 3-5 hours, cooled to room temperature, added with deionized water, and the pH is adjusted to neutral with aqueous ammonia. The aqueous phase is separated and collected, dried, and added to ethanol, stirred for 30-60 minutes, filtered, and dried on a rotary evaporator to obtain an asymmetrically branched fluorocarboxylic polyether.
2. The self-lubricating cutting fluid according to claim 1, characterized in that: The pH regulator refers to triethanolamine; the rust inhibitor refers to one of triethanolamine oleic acid soap or sodium lauryl sulfonate; the bactericide refers to one of phenylisothiazolinone or methylisothiazolinone; the extreme pressure and wear-resistant agent refers to one of phenol polyoxyethylene ether phosphate or 4,4-methylenebis(dibutyldithiocarboxamide).
3. The self-lubricating cutting fluid according to claim 1, characterized in that: In the above (1), the weight ratio of pentaerythritol, dimethyl carbonate, potassium carbonate and anhydrous tetrahydrofuran is 1:2.5-3.5:0.05-0.15:8-12, and the dilute hydrochloric acid refers to a hydrochloric acid aqueous solution with a concentration of 10%.
4. The self-lubricating cutting fluid according to claim 1, characterized in that: The weight ratio of ethyl acetate to anhydrous tetrahydrofuran used in each of the three ethyl acetate extractions in (1) is 1:2, and the gradient elution refers to the volume ratio of petroleum ether to ethyl acetate in the eluent of each step being 1:0, 30:1, 20:1, 10:1 to 5:
1.
5. The self-lubricating cutting fluid according to claim 1, characterized in that: In the (2), the weight ratio of pentaerythritol trimethyl carbonate, potassium hydroxide, ethylene oxide, propylene oxide and deionized water is 1:0.005-0.015:4-8:2-4:8-12, and the phosphoric acid solution refers to a 10% phosphoric acid aqueous solution.
6. The self-lubricating cutting fluid according to claim 1, characterized in that: The weight ratio of 1-iodoperfluorooctanoic acid, sodium hydroxide, tetrabutylammonium bromide and water / N,N-dimethylformamide mixed solution in (3) is 1:0.05-0.1:0.003-0.007:10-20.
7. The self-lubricating cutting fluid according to claim 1, characterized in that: The water / N,N-dimethylformamide mixed solution in (3) refers to a mixture of water and N,N-dimethylformamide in a weight ratio of 3:1, and the dilute hydrochloric acid refers to a hydrochloric acid aqueous solution with a concentration of 10%.
8. The self-lubricating cutting fluid according to claim 1, characterized in that: The weight ratio of the asymmetrically branched polyether, 1-hydroxytetradecafluorooctanoic acid, p-toluenesulfonic acid and toluene in (4) is 1:0.2-0.4:0.005-0.01:10-20, and the sodium bicarbonate solution refers to a sodium bicarbonate aqueous solution with a concentration of 5%.
9. The self-lubricating cutting fluid according to claim 1, characterized in that: The weight ratio of the asymmetrically branched fluoropolyether, maleic anhydride, xylene, deionized water and ethanol in (5) is 1:0.2-0.4:10-20:10-20:3-7.
10. The method for preparing the self-lubricating cutting fluid according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Add pH regulator and deionized water to the mixing kettle, stir at 200-300 rpm, mix for 5-10 min, add rust inhibitor, heat to 35-45 ° C, stir for 10-20 min, return to room temperature, add antibacterial agent and stir for 5-10 min to obtain a precursor solution; S2. Add asymmetrically branched fluorocarboxylic polyether to the precursor solution obtained in S1, stir at 500-700 rpm, mix for 10-20 minutes, then add extreme pressure and wear resistant agent, mix for 5-10 minutes to obtain a self-lubricating cutting fluid.